2019
DOI: 10.1101/723478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A loss-of-function mutation inItgalcontributes to the high susceptibility of Collaborative Cross strain CC042 toSalmonellainfections

Abstract: 25Salmonella are intracellular bacteria that are found in the gastrointestinal tract of mammalian, 26 avian, and reptilian hosts. They are one of the leading causes of foodborne infections and a major 27 threat for human populations worldwide. Mouse models have been extensively used to model 28 distinct aspects of the human Salmonella infections in vivo and have led to the identification of 29 several host susceptibility genes. We have investigated the susceptibility of Collaborative Cross 30 strains to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…A loss-of-function mutation in Itgal was found to account for the Tip2 QTL and explain a significant portion of the susceptibility of the CC042 line. This finding is consistent with that of a concurrent study that also identified Itgal to be underlying the susceptibility of CC042 mice to Salmonella enterica serovar Typhimurium (51). We previously found that Itgal deletion in the B6 mouse background resulted in a defect in T cell recruitment to the lung and an increased pulmonary M.…”
Section: Discussionsupporting
confidence: 92%
“…A loss-of-function mutation in Itgal was found to account for the Tip2 QTL and explain a significant portion of the susceptibility of the CC042 line. This finding is consistent with that of a concurrent study that also identified Itgal to be underlying the susceptibility of CC042 mice to Salmonella enterica serovar Typhimurium (51). We previously found that Itgal deletion in the B6 mouse background resulted in a defect in T cell recruitment to the lung and an increased pulmonary M.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, WSB/EiJ excelled in every facet of resilience against P. chabaudi AJ and maintained comparatively much lower iRBC densities ( Figure 2 ). Infection resilience in this mouse strain may generalise to other malaria parasites, including P. berghei ( Bopp et al, 2010 ), yet interestingly, these mice are highly vulnerable to Salmonella infections ( Zhang et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…KIAA0556 is associated with microtubule regulation in humans, and knockout mutations in humans and mice have been associated with the neurological disorder, Joubert syndrome [46]. ITGAL encodes integrin alpha L chain, and loss of function variants in this gene have been associated with compromised immunity including increased susceptibility to infection to Salmonella in mice [47]. Given that iterative association analysis failed to prioritise one of these variants over the other, it is unknown which of these variants might be responsible for the QTL, and our focus on protein-coding variants as candidates may have also overlooked alternative non-coding or structural mutations as responsible.…”
Section: Discussionmentioning
confidence: 99%